Effects of ventilation on leakage and diffusion law of gas pipeline in utility tunnel. (November 2020) - Zhang, Ping; Lan, Huiqing
Highlights: A CFD model of gas leakage and diffusion in utility tunnel is built. The formulas of gas diffusion time are derived, and the layout of the alarm can be reasonably selected. Effects of ventilation parameters on gas distribution law in gas tunnel are analyzed. The optimal selection of ventilation velocity and ventilation outlet's size is determined. Abstract: The gas pipeline in the utility tunnel locates at an underground closed space. Once the gas leaks, the accident consequence will be more serious. Therefore, it is very important to study the effect of ventilation on leakage and diffusion of the gas pipeline in the utility tunnel. This paper takes the gas pipeline in the utility tunnel in Songjiang District of Shanghai as the study object. Based on the computational fluid dynamics (CFD) theory, a simulation model of gas pipeline in the utility tunnel is established, and the scenarios of gas leakage and diffusion under different ventilation velocities and ventilation outlet's sizes are simulated respectively. The results show that: (1) Gas diffusion time has an exponential relationship with both ventilation velocity and side length of ventilation outlet. (2) Alarm time on the downwind side in the gas tunnel has a linear relationship with both ventilation velocity and ventilation outlet's size. (3) Gas volume ratio has a power function relationship with both ventilation velocity and side length of ventilation outlet. (4) Gas average concentration has an exponential relationship with ventilation velocity and a logarithmic relationship with side length of ventilation outlet, and the effects of ventilation velocity and ventilation outlet's size on the gas concentration along the distance are similar. (5) In practical engineering, it is an optimal selection that the ventilation velocity is between (5 m/s, 7 m/s) and the side length of ventilation outlet is between (1 m, 1.25 m).